Sinapis Semen: A review on phytochemistry, pharmacology, toxicity, analytical methods and pharmacokinetics - Dang, Rui; Guan, Huida; Wang, Changhong (Frontiers in Pharmacology, 2023)
Sinapis Semen (SS), the dried mature seed of Sinapis alba L. and Brassica juncea (L.) Czern. et Coss., is one of the traditional Chinese medicinal materials with a wide range of pharmacological effects being used for asthma, cough and many other ailments. SS is also widely used in food agriculture, medicine and other industries in North America and South Asia. More recently, the research on SS has gradually intensified and increased. However, there is no systematic review of SS. In this review, through literature exploration and analysis, the research advance on phytochemistry, pharmacology, toxicity, analytical methods and pharmacokinetics of SS was aggregated initially. Total 144 compounds have been isolated and identified from SS. Among them, glucosinolates and their hydrolysates and volatile oils are the main active ingredients and important chemical classification markers. SS has a wide range of pharmacological effects, especially in cough suppressing, asthma calming, anti-inflammatory, neuroprotective, cardiovascular protective, inhibiting androgenic effects, anti-tumor, and skin permeation promoting effects. Sinapine and sinapic acid are the main active ingredients of SS for its medicinal effects. However, SS has a strong skin irritation, presumably related to the time of application, the method of processing, and original medicinal plants. This review will provide useful data for the follow-up research and safe and reasonable clinical application of SS.